What Learning Means - National Endowment for the Humanities (NFAH), Washington, DC.; National Endowment for the Humanities (NFAH), Washington, DC. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1997)
This pamphlet describes seminars conducted by of the National Endowment for the Humanities (NEH) to expand teachers' knowledge at all levels in order to expand students' knowledge. The seminars include: teaching with technology; forging local partnerships; work outside the classroom; lifelong learning exhibitions; the civil war; castle, cathedral, pyramid, and Roman city; museum-school partnerships; and expanding learning through television. (EH)
Availability: National Endowment for the Humanities, 1100 Pennsylvania Avenue, NW, Washington, DC 20506; telephone: 202-606-8400; toll-free: 800-NEH-1121.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Resources; Cultural Centers; Educational Facilities; Elementary Secondary Education; Inservice Teacher Education; Museums; School Community Relationship; Technology; National Endowment for the Humanities; Information Analyses